Time‐resolved photoluminescence spectroscopy of charge transfer states in blends of pentacene and perfluoropentacene. Issue 7 (12th June 2017) - Broch, K.; Gerhard, M.; Halbich, M.; Lippert, S.; Belova, V.; Koch, M.; Schreiber, F.
Abstract : Charge transfer states in blends of organic semiconductors have significant importance for the functioning of organic optoelectronic devices, but are also interesting from the perspective of fundamental research as many of their properties as well as their influence on the photophysics of the material are not yet completely understood. We report on a time‐resolved photoluminescence study of the photophysics of the charge transfer state in the prototypical donor–acceptor system pentacene mixed with its perfluorinated counterpart. We find indications for the existence of two distinct charge‐transfer states, one of them formed in the bulk of the mixed phase, the other one formed at the interface to phase‐separated pentacene domains. We discuss the implications of the difference in temperature dependence of the emission intensity and the lifetime observed for these charge transfer states. Abstract : Using timeUsing time‐resolved photoluminescence spectroscopy the authors investigate the photophysics of charge transfer (CT) states in blends of pentacene with perfluoropentacene and find indications for the existence of two distinct CT states, one formed within tresolved photoluminescence spectroscopy the authors investigate the photophysics of charge transfer (CT) states in blends of pentacene with perfluoropentacene and find indications for the existence of two distinct CT states, one formed within the bulk of an intermixed phase and the second formed at the interface between phase separated pentacene domains and the mixed phase. The latter exhibits features which are consistent with mobile CT excitons migrating along the interface.